A Review of Ethnopharmacological Practices Among Two Indigenous Communities In Sumatra: The Anak Dalam And Mentawai Tribes - Anasri, Fadhil Mubarak; Syafri, Suryati (Universitas Ahmad Dahlan, 2025)
Indonesia is a country rich in biodiversity and high culture, including traditional knowledge such as the use of medicinal plants. This study examines ethnopharmacological practices in two indigenous communities on the island of Sumatra: the Anak Dalam tribe in Jambi and the Mentawai tribe in West Sumatra. The study reviewed several articles on medicinal plants on Google Scholar related to the plant species used, plant parts utilized, processing methods, and indications for their use in traditional medicine. The review results show that both tribes utilize various plants to treat ailments such as fever, diarrhea, coughs, wounds, digestive disorders, and infections. Some of these are supported by scientific evidence regarding their pharmacological activities, such as Zingiber officinale, Psidium guajava, Curcuma longa, and Eurycoma longifolia. The results of this review confirm that the traditional knowledge of both communities has excellent potential for development in pharmacy and conventional medicine. Documentation and scientific study of medicinal plants are crucial for cultural preservation and the development of traditional medicine.